A practical guide to the use of Narrow Band Imaging (NBI) in the early detection of oral cancer: case series and review of the literature - Guida Agostino; Perri Francesco; Annunziata Marco; Monteiro Luis; Warnakulasuriya Saman (Journal of Oral Medicine and Oral Surgery)
Oral Squamous Cell Carcinoma (OSCC) shows an overall 5 yr survival rate of just above 50%. With an estimated 390,000 new cases per year the current therapeutic approaches have failed in the past 20 yr to improve survival. Reducing the burden of this malignancy represents a challenge for clinicians around the globe. Early diagnosis represents the most effective option to reduce the impact of OSCC. Several chairside adjunctive techniques have been researched for the early diagnosis of OSCC but many of them have been found to have limited application due to their low sensitivity and specificity. Narrow Band Imaging (NBI) has the potential to be a useful aid for the clinician involved in the diagnosis and management of Oral Potentially Malignant Disorders (OPMDs) and OSCC. NBI fibroscopy is able to show microvasculature of oral lesions, possibly indicating the likelihood of malignant transformation. Yet, due to its high costs, the long learning curve, and the necessity for calibration of the users its application requires through careful investigation. We performed a review of the existing literature and, by showcasing some clinical cases, we aim to give the clinicians a practical guide to perform NBI when managing OPMD lesions of the different anatomical subsites of the oral cavity, based on the existing clinical evidence.